2004
DOI: 10.1504/ijep.2004.005683
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and the influence of sources on Paulinia (Brazil) and surroundings

Abstract: The air quality in the industrial area and surroundings of the city of Paulínia (state of São Paulo, Brazil) has been investigated by analysing the concentration of air pollutants (SO 2 , PM 10 , NO, NO 2 , CO and ozone) and identifying the main sources of air pollution. A mobile pollutant monitoring unit was used to collect the data at five different sites from November 2000 to July 2002. Critical pollutants were determined based on air quality standards, and sources were identified by principal component ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…1), which is composed of 19 municipalities with different types of land use (industrial, agricultural and urban areas). In addition to fo-rest fragmentation, the expansion of agricultural, urban and industrial areas in the MCR has led to increased pollutant emissions, such as sulfur and nitrogen dioxides (CE-TESB 2012) that acidify the rain (Tresmondi et al 2005). Unless the natural characteristics of the forest fragments increase the resilience against pollution impacts, the atmospheric contamination and acid rain may endanger the local soil and may affect many of the ecological processes in these remaining forest patches.…”
Section: Introductionmentioning
confidence: 99%
“…1), which is composed of 19 municipalities with different types of land use (industrial, agricultural and urban areas). In addition to fo-rest fragmentation, the expansion of agricultural, urban and industrial areas in the MCR has led to increased pollutant emissions, such as sulfur and nitrogen dioxides (CE-TESB 2012) that acidify the rain (Tresmondi et al 2005). Unless the natural characteristics of the forest fragments increase the resilience against pollution impacts, the atmospheric contamination and acid rain may endanger the local soil and may affect many of the ecological processes in these remaining forest patches.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the monitoring station at PC appropriately characterizes the study region and can be used as a reference to the correlation analysis (table 1). Studies conducted in the region (Tresmondi & Tomaz 2004, Boian & Andrade 2012, Bulbovas et al 2015 also showed little spatial variation in air pollution levels in the MRC, confirming the representativeness of the monitoring station in Paulínia Center for the study area.…”
Section: Resultsmentioning
confidence: 65%
“…The region economic growth initiated in the sixties with the implementation of large urban industrial complexes (Gutjahr 2004), as the city of Paulínia, which has a significant amount of mainly chemical and petrochemical industries (Tresmondi & Tomaz 2004). The MRC has been affected by high levels of primary air pollutants originated from road traffic and, is responsible for over 80% of CO, NOx and hydrocarbon emissions, and develops industrial activities that emit about 70% of the particulate matter present in the region (Ueda & Tomaz 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The typical behavior of wind direction in the MRC region during the day is: (a) in early morning and evening the predominant wind directions are SSE and SE; (b) in morning the predominat wind direction is SSE, SE and NE and (c) in the afternoon the NNE, SSE, N, SSW and S are the most frequent directions. Then prevalence winds are between east and south (CETESB, 2004;Tresmondi and Tomaz, 2004). As in the MRSP, during the dry season, the minimum relative humidity can be around 15%, mainly in September.…”
Section: Characterization Of Study Areamentioning
confidence: 99%
“…For the MRC there are few studies for ozone air pollution (Tresmondi and Tomaz, 2004). Martins et al (2006b) The aim of this work is to determine the interaction between these metropolitan regions concerning the evolution of ozone concentration.…”
Section: Introductionmentioning
confidence: 99%